Study and treatment proposal for an effluent generated in a slaughterhouse - Asanuma , Nícolas Kenji; dos Santos , João Pedro Guidolin; Polastri, Paula; Martins , Danielly Cruz Campos (Seven Editora, 2023)
The treatment of slaughterhouse effluent is extremely important due to the large organic and inorganic load that the wastewater carries after all the productive process developed in this industry segment. In its production, a large amount of water is used for the process of slaughter, cleaning of carcasses and sanitization, which generates a huge volume of effluent. The consumption of beef grows year by year in Brazil and in the world, so organizing an effective form of effluent treatment undoubtedly contributes to environmental preservation with regard to receiving bodies, such as rivers. The objective of this study was to elaborate a proposal for a treatment system based on the characterization of the effluent generated by the slaughterhouse. For this, it was necessary to collect data in relation to the production process, productive organization and forwarding of the waste generated. Based on the characterization of the raw effluent, an effluent treatment was proposed, taking into account the available literature, including preliminary treatment, with static and rotary sieve, primary treatment, with coagulation and flotation processes with organic coagulant, and secondary treatment using anaerobic, facultative ponds and, finally, a polishing pond playing the role of tertiary treatment. DOI:https://doi.org/10.56238/alookdevelopv1-153